Technologies for display application of liquid crystal light shutters. (11th February 2017) - Huh, Jae-Won; Yu, Byeong-Hun; Heo, Joon; Ji, Seong-Min; Yoon, Tae-Hoon
ABSTRACT: By switching a light shutter placed at the backside of a see-through display, we can select the transparent or high-visibility mode of the display panel. In this paper, we introduce technologies for liquid crystal (LC) light shutters that can scatter and absorb the incident light simultaneously, which is preferable for display applications. A light shutter for display applications can be realized in the normally-opaque mode by using a double-layered structure using cholesteric LCs or a single-layered structure using dye-doped cholesteric LCs. Whereas, it can be realized in the normally-transparent mode by using dye-doped polymer-networked LC cells using negative or positive LCs. Operation of each of the technologies is reviewed and the performance of these technologies is compared in this paper.